Digital Memory on Ayotzinapa: Tlatelolco and the Rewriting of the Narrative of the Recent Past (Clepsidra - Interdisciplinary Journal of Memory Studies, 2025)
This article explores digital participation on Twitter surrounding the Ayotzinapa case and how it contributed to the creation of an affective memory and the construction of a counter-narrative in response to political violence in Mexico. The study focuses on the connection between the disappearance of the 43 Ayotzinapa students in 2014 and the Tlatelolco massacre in 1968, examining how this relationship was viralized on social media, creating a bridge between two emblematic events of state repression. Using a database of over 2.4 million tweets, a quantitative and qualitative analysis was conducted to better understand the content of Twitter conversations about Ayotzinapa. The research explores how the viralization of these narratives challenges Mexico’s media monopoly and enables the emergence of alternative and emancipatory discourses in the digital space.
Keywords: Ayotzinapa, Tlatelolco, Digital activism, Twitter